Pengaruh Pemberian Akupresur Titik P6 pada Ibu Trimester I dengan Emesis Gravidarum di Hiroshima, Japan - Diah Dinanti; Rani Safitri (Jurnal Ilmiah Kedokteran dan Kesehatan, 2025)
Emesis gravidarum is one of the complaints that commonly occur in the first trimester of pregnancy and can interfere with the comfort and daily life of pregnant women. The use of non-pharmacological therapies such as P6 point acupressure is a potential alternative to reduce such complaints without pharmacological risks to the fetus. This study aims to analyze the effectiveness of P6 point acupressure on the reduction of symptoms of emesis gravidarum in pregnant women in the first trimester. The study used a quasi-experimental design with a pretest-posttest control group approach. Twenty respondents were divided into two groups: the intervention group that received P6 point acupressure and the control group without intervention. Symptom measurements were carried out before and after treatment for five consecutive days. The results of the analysis using the Wilcoxon Signed Ranks test showed that the intervention group experienced a significant decrease in symptom scores (p = 0.002), while the control group showed an increase in symptoms (p = 0.013). These findings suggest that P6 point acupressure is effective in reducing symptoms of emesis gravidarum and can be used as a safe complementary intervention in obstetric services, especially in the early stages of pregnancy.